Intention to breast feed from a social marketing perspective: a case study at Hospital Sultan Abdul Halim / Noor Ain Mohd Zuki and Siti Zuhasniza Mohd Zin - Mohd Zuki, Noor Ain; Mohd Zin, Siti Zuhasniza (2010)
This research concerns the issue of intention to breast feed from a social marketing perspective, which involves a case study at Sungai Petani Hospital. The objectives of conducting this research are to determine the relationship between knowledge, beliefs, referent others and social acceptability toward the intention to breast feed and to identify the most significant factor that influence the intention of women to breast feed in Sungai Petani, Kedah. Specifically this research is conducted at Unit Obstetrik Hospital Sultan Abdul Halim, Sungai Petani, Kedah. A total of 100 respondents were selected to fill in the questionnaire that consists of five sections. This study uses the systematic sampling which involves drawing every 3rd element in the population starting with a randomly chosen element between 1 and 3. The data was analyzed with inferential statistic and Multiple Regression of Statistical Package for Social Sciences (SPSS) version 16.0. For the data analysis and hypotheses testing, researchers found that the four independent variables have significant relationship toward the intention to breastfeed and the social acceptability is the most influence factor.